Analysis Of Internal Control Of Accounts Receivable To Minimize Doubtive Accounts Receivable At JIH Hospital Yogyakarta - Salma Az-Zahra; Nurfauziah, Nurfauziah (International Journal of Economics, Business and Innovation Research, 2025)
Internal control of accounts receivable is a process designed and implemented by a company to ensure that receivables can be collected and received on time. If the payment of receivables is not received within the stipulated time, it can impact the company's financial condition. JIH Hospital faces challenges in managing receivables as it provides payment options through third parties, namely insurance companies. The payment mechanism by insurance companies is carried out within a certain period after healthcare services are provided or after patients are discharged following treatment. Therefore, JIH Hospital needs to apply effective receivables control to minimize the risk of prolonged payment delays and to avoid the potential for uncollectible receivables. This study aims to examine how internal control over receivables is implemented at JIH Hospital and to assess the quality of the receivables collection process. The research uses a qualitative approach by conducting in-depth interviews with individuals directly involved in the collection process. The analysis is based on the COSO framework, which consists of five main components: control environment, risk assessment, control activities, information and communication, and monitoring. The results indicate that internal control at JIH Hospital has been effectively applied through the categorization of receivables using an aging schedule and strict supervision in the collection process. However, several weaknesses were identified, such as limited flexibility in handling special cases and restricted access to information in certain work areas. Based on these findings, it can be concluded that the internal control applied is quite effective but needs to be improved by enhancing communication systems, conducting regular monitoring, and implementing more adaptive policies in managing problematic receivables.